Information Technologies in Education: Forming the Competences of the Future - A. Averin, Sergey; A. Alisov, Evgenii; S. Murodhodjaeva, Natalia; A. Noskov, Igor; V. Tsaplina, Olga; E. Osipenko, Lyudmila (International Journal of Engineering and Technology, 2018)
Specialists in the field of programming create a huge flow of software, which is mainly aimed at attracting children to specific software products that have a developing effect, rather, as a side effect. The developing effect is not diagnosed in such programs, but it is often declared by the developers. Scientific and methodological response of the pedagogical community to information challenges in the field of preschool education was the creation of the methodology of author's children's animation and the corresponding educational module. In the article two important competences of preschool children are considered, which are basic in relation to many other competences formed at an older age: developed imaginative thinking and developed research abilities. The development of these competences projects as a methodical waymark for the technical development of the methodology of author's children's animation.Thereby, the purpose of the article is to justify the creation of methods for author's children's animation that determines the development of imaginative Â thinking and research abilities of preschool-age children, taking into account the requirements of the modern information society.To achieve this goal, the following methods were used: content analysis; method of contrastive-comparative analysis of scientific and methodical materials; method of system analysis; method of mathematical and statistical data processing; expert appraisement, generalization of research results.Based on the results of the study, the theoretical foundations of the preschool-age child's competence were determined, a pilot study of the development of preschoolers' competencies, the development and introduction of the educational module "Multstudio I CREATE THE WORLD" into the practice of pre-school pedagogy as a potentially effective means of developing imaginative thinking and research abilities of children, development of recommendations for software providing multstudios in kindergarten.Â